2018
DOI: 10.4220/sykepleiens.2018.71857
|View full text |Cite
|
Sign up to set email alerts
|

Lindring av polynevropati etter cellegift

Abstract: En vanlig seneffekt etter kreftbehandling er cytostatikaindusert perifer polynevropati (CIPP). Denne artikkelen redegjør for en tverrfaglig tilnaerming til lindring av CIPP.Cytostatikaindusert perifer polynevropati (CIPP) kan vaere en plagsom seneffekt etter kreftbehandling. Sykepleieren har en viktig rolle når det gjelder å kartlegge symptomer og iverksette tiltak. Sykepleieren kan også ta initiativ til samarbeid med annet helsepersonell der pasienten kan ha nytte av et tverrfaglig tilbud.Cytostatikabehandlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…However, the dissolution of minerals by oxidants releases more high-valence cations (e.g., Mg 2+ , Si 2+ , Ca 2+ , Al 3+ , or Fe 3+ ) into the solution, enhancing the bridging effect and leading to more attraction between oil and rock. The impact of the high-valence cations has been exemplified in a study by Haugen and Fjelde et al Haugen found that the presence of Fe 3+ in the brine can alter the wettability of the rock to more oil-wet conditions, and it had more significant impact on wettability than Ca 2+ when the concentrations of the cations are the same. Fjelde et al investigated the effect of cation bridging by Fe 3+ on the rock wettability, and they observed that a Fe 3+ concentration as low as 50 ppm could alter the wettability of clay to more oil-wet conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, the dissolution of minerals by oxidants releases more high-valence cations (e.g., Mg 2+ , Si 2+ , Ca 2+ , Al 3+ , or Fe 3+ ) into the solution, enhancing the bridging effect and leading to more attraction between oil and rock. The impact of the high-valence cations has been exemplified in a study by Haugen and Fjelde et al Haugen found that the presence of Fe 3+ in the brine can alter the wettability of the rock to more oil-wet conditions, and it had more significant impact on wettability than Ca 2+ when the concentrations of the cations are the same. Fjelde et al investigated the effect of cation bridging by Fe 3+ on the rock wettability, and they observed that a Fe 3+ concentration as low as 50 ppm could alter the wettability of clay to more oil-wet conditions.…”
Section: Resultsmentioning
confidence: 99%
“…These data and an auxiliary environmental dataset were used to compute sewer conditions. Sewer conditions were divided into good, intermediate, and bad conditions based on the study of Haugen and Viak [31]. Specifically, for the Ålesund sewer network, 10 physical factors (i.e., age, diameter, depth, length, slope, material, pipe type, network type, pipe form, and connection type) and 10 environmental factors (i.e., rainfall, geology, landslide area, population density, land cover, building area, groundwater level, traffic volume, road network, and soil type) were aggregated and assigned for each sewer pipe.…”
Section: Data and 3d Model Preparationmentioning
confidence: 99%